Left Chronic Otitis Media with Squamous Cell Carcinoma of the Middle Ear and Postauricular Mastoid Fistula: A Case Report - Shreedhar Prasad Acharya; Chetana Pathak; Sandarva Giri; Meera Bista; Deependra Mandal (Journal of Nepal Medical Association, 2020)
Though squamous cell carcinoma is the commonest tumor, it rarely presents in the middle ear and follows a history of chronic ear discharge. Postauricular mastoid fistula is also a rare complication of chronic otitis media. These two pathological changes occurring simultaneously are even rarer. We report a rare case of a 37 years old male with a history of left-sided chronic ear discharge and conductive hearing loss. Squamous cell carcinoma along with postauricular mastoid fistula was diagnosed based on high-resolution computed tomography scan and histopathology. Left modified radical mastoidectomy with tympanic membrane grafting was done under general anesthesia. Often middle ear tumor is associated with long-standing ear discharge and this case is a very good example. The co-occurrence of the middle ear tumor with mastoid fistula is extremely rare as both the entities are rare in itself.